The reduction of chromite ore processing residues by green tea synthesized nano zerovalent iron and its solidification/stabilization in composite geopolymer. (10th October 2019) - Muhammad, Faheem; Xia, Ming; Li, Shan; Yu, Xu; Mao, Yanhong; Muhammad, Farooq; Huang, Xiao; Jiao, Binquan; Yu, Lin; Li, Dongwei
Abstract: The present study is aimed to reduce the environmental footprints resulted from chromite ore processing residues (COPR); a hazardous waste having Cr(VI). The solidification/stabilization of COPR through geopolymer coupled with green tea synthesized nano zerovalent iron (GT-NZVI) is an effective approach to deal with this challenge. Therefore, the blast furnace slag and metakaolin were used to prepare the composite based geopolymer and GT-NZVI particles were synthesized by oolong tea in current experiment. The GT-NZVI treated and untreated COPR was solidified in composite geopolymer. The efficiency of solidified products was evaluated through compressive strength and leaching analysis. The results depicted that varying sizes of GT-NZVI particles were successively synthesized which could be utilized for reduction of Cr(VI) existed in COPR. The solidified products having GT-NZVI treated COPR (GCM (GT-NZVI) and untreated COPR (GCM) had compressive strength of 33Mpa and 47 MPa, respectively up to 50% addition of COPR waste. The immobilization effect of GCM (GT-NZVI) samples were better than GCM samples. The leaching toxicity of Cr(VI) in both GCM (GT-NZVI) and GCM samples was far below than safe limits(<5 mg/L). In addition, the fourier transform infrared spectrometry, X-Ray diffraction, scanning electron microscope equipped with energy dispersive spectrometer analysis had verified that COPR was effectively solidified in composite based geopolymer by physical and chemical means. Graphical abstract: Image 1027 Highlights: The synthesize nano zerovalent iron by green tea (GT-NZVI). Reduction of chromium existed in chromite ore processing residues (COPR) by GT-NZVI. Significant results are achieved regarding compressive strength and Cr (VI) solidification. Comparatively, GT-NZVI treated COPR has better solidification than untreated COPR.